2018
DOI: 10.1186/s12991-018-0174-6
|View full text |Cite|
|
Sign up to set email alerts
|

Suicide ideation and attempts among people with epilepsy in Addis Ababa, Ethiopia

Abstract: BackgroundSuicidal ideation and attempts are more frequent in people with epilepsy than in general population and suicide attempt increases the chance of later completed suicide. The aim of this study was to assess the prevalence and associated factors of suicidal ideation and attempt among people with epilepsy in Amanuel Mental Specialized Hospital, Addis Ababa, Ethiopia.MethodsInstitution-based cross-sectional study was conducted from May to June 2014 at Amanuel Mental Specialized Hospital among people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
32
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 33 publications
12
32
2
5
Order By: Relevance
“…Hypochondriasis is the most symptom of depression seen in 97% of depressed patients. Suicidal ideation was observed in only 22% of this patients, in line with studies from Ethiopia with 29.8% (Haile et al, 2018) and Egypt with 23.5% (Hamed et al, 2012a) but higher than in literature (Jones et al, 2003), Andrijić in Bosnia (Andrijić et al, 2014) with 14% and in USA (Hecimovic et al, 2012) with 11.9%. In opposition, highest prevalence of suicidal ideation was observed in studies from Cuba Havana with 45.2% (Espinosa et al, 2010) and Egypt with 55% (Hamed et al, 2012b).…”
Section: Clinical Presentation Of Depressive Symptomssupporting
confidence: 86%
“…Hypochondriasis is the most symptom of depression seen in 97% of depressed patients. Suicidal ideation was observed in only 22% of this patients, in line with studies from Ethiopia with 29.8% (Haile et al, 2018) and Egypt with 23.5% (Hamed et al, 2012a) but higher than in literature (Jones et al, 2003), Andrijić in Bosnia (Andrijić et al, 2014) with 14% and in USA (Hecimovic et al, 2012) with 11.9%. In opposition, highest prevalence of suicidal ideation was observed in studies from Cuba Havana with 45.2% (Espinosa et al, 2010) and Egypt with 55% (Hamed et al, 2012b).…”
Section: Clinical Presentation Of Depressive Symptomssupporting
confidence: 86%
“…Participants who have poor social support was contributed to greater perceived stress and depression. They also go through stressful conditions and unable to cope with this easily [44].Studies revealed that providing good social support can protect individuals from the feeling of suicidal thought and attempt, worthiness during the times of an unstable situation and decreases feelings of despair [45,46]. This is evidenced in the previous community-based study in Ethiopia showed that providing a high level of psychological support protect the individuals from developing common mental illness by 50% [47].…”
Section: Discussionmentioning
confidence: 95%
“…It was also more common among generalized seizures in contrast to partial seizures [54] and associated with a poor course of the seizure disorder [55]. Frequent seizure attacks increase suicidal ideation and attempt among people living with epilepsy [46]. Comorbid mental illness affects negatively health-related quality of life and clinical course of epilepsy [56].…”
Section: Discussionmentioning
confidence: 99%
“…After publication of the article [ 1 ], it has been brought to our attention that an author’s name was spelt incorrectly in the original published article. Getinet Ayano was previously spelt “Getnet Ayano”.…”
Section: Correction To: Ann Gen Psychiatry (2018) 17:4 101186/s12991mentioning
confidence: 99%